DAMPAK KEMATANGAN EMOSI DAN DISIPLIN KERJA PADA KINERJA DOSEN DI 4 PTS DI KOTA BANDAR LAMPUNG - Andy FitriyadI Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Emotional maturity is one's ability to recognize oneself, manage oneself, motivate oneself,recognize the emotions of others (empathy) and the ability to build relationships with others. WhilePerformance is the result of the process of a work activity undertaken based on measurement andassessment of the results of activities.In this research also object of research used is four (4) Private University (PTS) in BandarLampung city, as research object Some of the causal factors used in this research include emotionalmaturity and work discipline as trigger factor which according to some similar research have influenceThe great Sri (1999) and Sia (2001). In terms of the importance of emotional maturity and workdiscipline as an important factor for shaping performance, the research model used is: